Lipid-Polymer Hybrid Nanoparticles for Controlled Delivery of Hydrophilic and Lipophilic Doxorubicin for Breast Cancer Therapy [Erratum] - Tahir N (Dove Medical Press, 2020)
Tahir N, Madni A, Correia A, et al. Int J Nanomed.  2019;14:4961– 4974.  On page 4967, Figure 3 artwork is incorrect, Figure 4 artwork was mistakenly added by the Editorial staff during the publication process.Read the original article